PEWARISAN DALAM SISTEM HUKUM DI INDONESIA - GINA ANGGRAENI GINA; Deni Ariyanto; Mohamad Aan Ansori; Achmad Nurjannah (UI Cirebon (Universitas Islam Cirebon), 2020)
ABSTRACK This study aims to understand about the types of inheritance that exist in Indonesia and where the inheritance certificate is made. The method used is library research using legal materials in the form of statutory regulations, legal materials such as books written by experts and selected relevant legal book authors, other legal materials that can provide instructions or explanations. The results of the study indicate that there are still classifications in the inheritance law system in Indonesia, considering the plurality of laws in Indonesia, the division of these groups is still recognized for its existence until now, so the applicable inheritance law also follows these groups. First, the law of inheritance according to the Civil Code or BW, for European and eastern foreign residents of Chinese descent. Second, the law of inheritance according to Islam, for citizens who are Muslim. The third, the law of inheritance according to local customary law.